Impact of commonly used Ag-Cu ion doses onDesulfovibriosp.: growth and microbiologically induced corrosion against stainless steel - Arkan-Ozdemir, S.; Cansever, N.; Ilhan-Sungur, E. (IWA PUBLISHING, 2020)
Ag-Cu ions in cooling water may inhibit the activity of sulfate-reducing bacteria and therefore provide solutions to microbiologically induced corrosion (MIC) problems, mainly caused byDesulfovibriosp. To investigate this, the MIC behavior ofDesulfovibriosp. on 316L stainless steel in terms of growth and extracellular polymeric substances (EPS) production was investigated in the presence of Ag-Cu ions. Laboratory-scale systems were set up with final concentrations of 0.13 ppm Ag and 0.3 ppm Cu ions, as they are the frequently used doses for cooling waters, and operated over 720 hours. The corrosion rate was evaluated by gravimetric assay, scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) analyses. The growth ofDesulfovibriosp. was assessed by bacterial counting and EPS production. Ag-Cu ions in the biofilm were assessed by inductively coupled plasma - optical emission spectrometry (ICP-OES) and EDS-elemental mapping analyses. It was concluded that the ion concentrations used caused an increase in EPS production, especially of protein. The corrosion rate of the metal byDesulfovibriosp. in the presence of ions was detected as being 29 times higher than that in the sterile medium with the ions after 720 hours. The results suggested thatDesulfovibriosp. exhibited more corrosive behavior in the presence of non-toxic concentrations of Ag-Cu ions.
Keywords: Ag-Cu ions; cooling water; corrosion rate; Desulfovibriosp; extracellular polymeric substances; microbiologically induced corrosion; SULFATE-REDUCING BACTERIA; COPPER-SILVER IONIZATION; FRESH-WATER STRAIN; GALVANIZED STEEL; COOLING-TOWER; DESULFOVIBRIO SP; CARBON SOURCE; HEAVY-METALS; TOXIC METALS; LEGIONELLA; Engineering; Environmental Sciences & Ecology; Water Resources